2021
DOI: 10.1186/s12864-021-07889-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Babesia rossi infection induces hemolytic, metabolic, and viral response pathways in the canine host

Abstract: Background Babesia rossi is a leading cause of morbidity and mortality among the canine population of sub-Saharan Africa, but pathogenesis remains poorly understood. Previous studies of B. rossi infection were derived from clinical cases, in which neither the onset of infection nor the infectious inoculum was known. Here, we performed controlled B. rossi inoculations in canines and evaluated disease progression through clinical tests and whole blood transcriptomic profiling. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 102 publications
2
10
0
Order By: Relevance
“…The same studies showed similar transient increases in CXCL1-like concentration four days after infection, followed by decrease to a low level [ 27 , 93 ]. According to Smith et al [ 93 ], increased production of IL-10 may be a possible explanation for a decrease in IL-8. This speculation is supported by the results of Galán et al [ 30 ], who observed a negative correlation between IL-8 and hematocrit and increased levels of this chemokine even on the seventh day of the disease.…”
Section: Phagocytosismentioning
confidence: 75%
See 4 more Smart Citations
“…The same studies showed similar transient increases in CXCL1-like concentration four days after infection, followed by decrease to a low level [ 27 , 93 ]. According to Smith et al [ 93 ], increased production of IL-10 may be a possible explanation for a decrease in IL-8. This speculation is supported by the results of Galán et al [ 30 ], who observed a negative correlation between IL-8 and hematocrit and increased levels of this chemokine even on the seventh day of the disease.…”
Section: Phagocytosismentioning
confidence: 75%
“…Surprisingly, IL-8 levels have previously been reported as lower in dogs naturally infected with B. rossi in comparison to healthy dogs [ 28 ]. A possible explanation for this observation was missing the peak chemokine concentration, and later studies on experimental B. rossi infections have confirmed this supposition [ 27 , 93 ]. In dogs infected with B. gibsoni , both an increase and a decrease in IL-8 levels have been observed [ 94 ], while a transient increase of CXCL1-like has been reported, similar to IL-8, in B. canis infection.…”
Section: Phagocytosismentioning
confidence: 99%
See 3 more Smart Citations